Opinions of key stakeholders concerning involuntary admission of patients under the Mental Health Act 2001. (12th February 2016) - Georgieva, I.; Bainbridge, E.; McGuinness, D.; Keys, M.; Brosnan, L.; Felzmann, H.; Maguire, J.; Murphy, K.; Higgins, A.; McDonald, C.; Hallahan, B.
Abstract : Objectives: To evaluate and compare the opinions of key stakeholders involved in the involuntary admission and treatment of patients under the Mental Health Act (MHA) 2001 regarding their views towards the operation of the legislation. Methods: We employed a descriptive survey design. A questionnaire was distributed to stakeholders involved in the operation of the MHA 2001 (except service users, whose views were explored in a separate qualitative study) via paper or online versions evaluating their opinions regarding the operation of the MHA 2001 in relation to assessment, care, rights, transfer and information available. Results: Stakeholders agreed that in their opinion that patients generally benefit from the care they receive (79%) and that the MHA 2001 ensures an independent and fair review of the person's detention (65%). However, only 23% of stakeholders were satisfied with the process of transferring patients to hospital and with the clinical assessment procedures therein (37%), with the greatest levels of dissatisfaction amongst Gardai (Police), general practitioners (GPs) and family members. Conclusions: While the introduction of the MHA 2001 has assisted delivery of care to patients with improved adherence to international human rights frameworks applicable at the time of its enactment, substantial dissatisfaction with the implementation of the MHA 2001 in practice is experienced by stakeholders particularly at the distressing phase of clinical assessment and transfer to hospital.